2018
DOI: 10.1038/s41419-018-1065-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of SIRT6 triggers lethal autophagy in human cancer cells

Abstract: Sirtuin 6 (SIRT6) is a member of the NAD+-dependent class III deacetylase sirtuin family, which plays a key role in cancer by controlling transcription, genome stability, telomere integrity, DNA repair, and autophagy. Here we analyzed the molecular and biological effects of UBCS039, the first synthetic SIRT6 activator. Our data demonstrated that UBCS039 induced a time-dependent activation of autophagy in several human tumor cell lines, as evaluated by increased content of the lipidated form of LC3B by western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 52 publications
(65 reference statements)
3
55
0
Order By: Relevance
“…SIRT6 activated the AMPK pathway by regulating H3K9ac and H3K56ac in podocytes, thus preventing ROS-induced mitochondrial dysfunction and apoptosis (34). Furthermore, SIRT6 promoted autophagy through the ROS-mediated activation of the AMPK pathway in cancer cell lines (35). In the present study, ROS inhibition showed a stronger association with the expression Warburg effect-related genes than AMPK activation.…”
Section: Discussionsupporting
confidence: 45%
“…SIRT6 activated the AMPK pathway by regulating H3K9ac and H3K56ac in podocytes, thus preventing ROS-induced mitochondrial dysfunction and apoptosis (34). Furthermore, SIRT6 promoted autophagy through the ROS-mediated activation of the AMPK pathway in cancer cell lines (35). In the present study, ROS inhibition showed a stronger association with the expression Warburg effect-related genes than AMPK activation.…”
Section: Discussionsupporting
confidence: 45%
“…Activator SIRT1 [166,167] No report 4 UBCS039 Activator SIRT5 and SIRT6 [168] Inducing autophagy-associated cell death in cervix, colon and lung cancer [169].…”
Section: Srt2104mentioning
confidence: 99%
“…In healthy mammalian cells, the dominant activity is directed towards intracellular homeostatic turnover of proteins, mediating self-renewal energy generation, metabolism, and cell death [104][105][106]. New evidence has reported that many diseases are connected to autophagy, including primary cancer origins [107]. Autophagy activation insures and protects cancer cells, and this process in known as adaptive autophagy, which is directly associated with CDK5.…”
Section: Function Of Cdk5 In Autophagymentioning
confidence: 99%